ENT300 D'Love Beauty Spa / Fatma Zawani Abdul Hai... [et al.] - Abdul Hai, Fatma Zawani; Kamil, Errafazira; Morni, Nurjehan; Suhut, Syawalati; Azaman, Saidatul Nabillah (2014)
We named our business as D’Love Beauty Spa where we provided beauty center for the customers. Our beauty center use different concept of service compared to other beauty center which make us really unique. The customer will be serviced using the same concept as combination of modern and traditional, which are they be charged by the spa packages. We also collaborate with Majlis Agama Islam Sarawak (MAIS) to get our halal certificate. Our priority is to serve the best and excellent service and communication to our customer in term of quality and performance expectation. Also not forgot the services our beauty center will give a discount to our regular customer. Our employee will be professionally train to serve their customers to the fullest satisfaction. We ventured this business because we want to be the first entrepreneur that serves the beauty center by using the modern and traditional concept in term of service. Our business is long term because of highest population in Kota Samarahan and the less competitors in that market size. In fact, the beauty center is a well-known service in Malaysia and suitable for all gender and make us ventured this type of business. Thus, we strongly believe that our business will success as we serve various type of package for our beauty center and our business will separate throughout the world.